Relationship between telomere length and the prognosis of breast cancer based on estrogen receptor status: A Mendelian randomization study - Li, Yilun; Ma, Li (Frontiers in Oncology, 2022)
Abstract: Objective: To identify the relationship between telomere length and the prognosis of breast cancer with different status of estrogen receptor (ER). Methods: We collected single nucleotide polymorphisms (SNPs) associated with telomere length and breast cancer prognosis from the MRCIEU GWAS database and the dataset of a large meta-analysis conducted by the Breast Cancer Association Consortium (BCAC), respectively. The relationship was identified using inverse-variance weighted (IVW), MR-Egger, weighted median, penalized weighted median, and maximum likelihood methods. IVW, MR-Egger, and MR-PRESSO methods were used to perform sensitivity analysis to assess the accuracy of the results. Results: Telomere length was negatively associated with the prognosis of total breast cancer (odds ratio [OR]=1.84, 95% confidence interval [CI]=1.08-3.14, IVW method), especially with ER- breast cancer (OR=1.89, 95% CI=1.11-3.22, IVW method). No similar relationship was found between telomere length and the prognosis of ER+ breast cancer (OR=0.99, 95% CI=0.62-1.58, IVW method). The findings from other methods were consistent with the results shown by the IVW method. The Mendelian randomization assumptions did not appear to be violated. Sensitivity analysis indicated that the result was robust, and no bias was observed in the study. Conclusion: Telomere length is associated with the prognosis of total breast cancer, especially with ER- breast cancer. There is no significant correlation between telomere length and the prognosis of ER+ breast cancer. These findings add to the evidence that long telomere could predict a poor prognosis of ER- breast cancer.